Effects of Management on the Profitability of Seasonal Fisheries - Ben-Hasan, Abdulrahman; Walters, Carl; Sumaila, U. Rashid (Frontiers in Marine Science, 2019)
Seasonal fisheries emerge due to a variety of mechanisms: ontogenetic shifts of fish life stages, regulatory initiatives (e.g., fishing seasons) and/or biomass dynamics where there can be a strong seasonal reduction in stock biomass as fisheries harvest a single or double recruiting cohorts each year. The latter mechanism involves targeting species with biological traits including fast growth, high natural mortality and short lifespans; these fisheries have been expanding rapidly over the last forty years, gaining social and economic importance. In this paper, we underscore the biological and economic dynamics of these fisheries by developing an intraseasonal bioeconomic model to examine the profitability under two situations: open-access and limited entry. We also incorporate the opportunity cost—the earnings that would result from pursuing other lines of work—in our modeling framework. We show that under limited entry situation, profitability is maximized over a given season—when income just balances operating cost per effort. Under open-access, however, net profit per vessel is driven down until it equals the opportunity cost. Biologically, our approach suggests that higher income from alternatives to fishing leads to less biomass depletion than would occur if there were no alternative income sources. To conclude, we discuss several traditional regulatory options and their effects on the distribution of fishing effort and season length.